Intensified immunosuppressive therapy in patients with immune checkpoint inhibitor-induced myocarditis - Jennifer Cautela; Mélanie Gaubert; Michael Peyrol; Franck Paganelli; Laurent Bonello; Fabrice Barlesi; Sarah Zeriouh; Marc Laine; Nathalie Lalevee (Journal for ImmunoTherapy of Cancer)
Background Myocarditis is a rare but life-threatening adverse event of cancer treatments with immune checkpoint inhibitors (ICIs). Recent guidelines recommend the use of high doses of corticosteroids as a first-line treatment, followed by intensified immunosuppressive therapy (IIST) in the case of unfavorable evolution. However, this strategy is empirical, and no studies have specifically addressed this issue. Therefore, we aimed to investigate and compare the clinical course, management and outcome of ICI-induced myocarditis patients requiring or not requiring IIST.Methods This case–control study included all patients consecutively admitted to The Mediterranean University Center of Cardio-Oncology (Aix-Marseille University, France) for the diagnosis of ICI-induced myocarditis according to Bonaca’s criteria and treated with or without IIST. In addition, we searched PubMed and included patients from previously published case reports treated with IIST in the analysis. The clinical, biological, imaging, treatment, all-cause death and cardiovascular death data of patients who required IIST were compared with those of patients who did not.Results A total of 60 patients (69±12 years) were included (36 were treated with IIST and 24 were not). Patients requiring IIST were more likely to have received a combination of ICIs (39% vs 8%, p=0.01), and developed the first symptoms/signs of myocarditis earlier after the onset of ICI therapy (median, 18 days vs 60 days, p=0.002). They had a significantly higher prevalence of sustained ventricular arrhythmia, complete atrioventricular block, cardiogenic shock and troponin elevation. Moreover, they were more likely to have other immune-related adverse events simultaneously (p<0.0001), especially myositis (p=0.0002) and myasthenia gravis (p=0.009). Patients who required IIST were more likely to die from any cause (50% vs 21%, p=0.02). Among them, patients who received infliximab were more likely to die from cardiovascular causes (OR, 12.0; 95% CI 2.1 to 67.1; p=0.005).Conclusion The need for IIST was more common in patients who developed myocarditis very early after the start of ICI therapy, as well as when hemodynamic/electrical instability or neuromuscular adverse events occurred. Treatment with infliximab might be associated with an increased risk of cardiovascular death.